Implementation of the Electronic-Based Government System Policy in Basic Education Services in Sumedang Regency (International Forum of Researchers and Lecturers, 2025)
The implementation of the SPBE (Electronic-Based Government System) policy in basic education services through the New Student Admission (PPDB) at the Education Office of Sumedang Regency has faced several challenges. This study aims to examine how the SPBE policy is applied in one of the regional agencies in Sumedang. The research used a descriptive qualitative method with Edward III's Policy Implementation theory, which includes four dimensions: Communication, Resources, Disposition, and Bureaucratic Structure. The findings revealed that the SPBE policy implementation through PPDB is progressing well despite budget constraints. Creativity, innovation of human resources, leadership support, available SOPs, and regulations contributed to successful implementation. Supporting factors for this policy included strong leadership commitment, monitoring and evaluation after each PPDB, and quick responses from the Education Office regarding regulatory changes. However, the barriers to implementation were the involvement of high-ranking officials at both the Regency and Provincial levels, dependency on other parties for registration applications, and insufficient digital literacy among target groups. The Sumedang Regency Government has undertaken various efforts to overcome these barriers, including using social media for socialization, cross-checking with policymakers and implementers, providing suggestion boxes (manual and digital), and maintaining a quick response to policy changes. Additionally, schools have played a role in socializing the policy to target groups to anticipate potential issues.